Molecular spectrum of laterally coupled quantum rings under intense terahertz radiation - Baghramyan, Henrikh M.; Barseghyan, Manuk G.; Laroze, David (Scientific reports, 2017)
We study the influence of intense THz laser radiation and electric field on molecular states of laterally coupled quantum rings. Laser radiation shows the capability to dissociate quantum ring molecule and add 2-fold degeneracy to the molecular states at the fixed value of the overlapping size between rings. It is shown that coupled to decoupled molecular states phase transition points form almost a straight line with a slope equal to two. In addition, the electric field direction dependent energy spectrum shows unexpected oscillations, demonstrating strong coupling between molecular states. Besides, intraband absorption is considered, showing both blue and redshifts in its spectrum. The obtained results can be useful for the controlling of degeneracy of the discrete energy spectrum of nanoscale structures and in the tunneling effects therein.